EFFECT OF FERTILIZER TREATED RHIZOBIUM SP. AND AZOTOBACTER SP. ON INDOLE ACETIC ACID (IAA) PRODUCTION AND INDUCING VEGETATIVE CHARACTERISTICS OF ARACHIS HYPOGAEA - KULANDAIVEL, S.; PRAKASH, R. (Innovare Journal of Life Sciences, 2014)
The Indole – 3 – acetic acid (IAA) production was found to be mazimum as 1.86 ug/ml and 1.29ug/ml by Azotobacter sp. and Rhizobium sp. respectively. The results reveal that the wild types of (RT3 and AT3) Rhizobium sp. and Azotobacter sp. produced good vegetative characteristics increased root length and shoot length of seedlings. Fertilizer treated Rhizobium sp. and Azotobacter sp. (mutants) produced only decreased shoot length, root length and number of nodules formed in Arachis hypogaea when compared to wild type. Key words: Azotobacter sp., Rhizobium sp., IAA, Fertilizer, Arachis hypogaea.